114k views
0 votes
-x+y(x-4)x

X=-5 Y=-2

2 Answers

5 votes

Answer:

-85

Explanation:

-(-5)+(-2)(-5-4)(-5)

5-2(-9)(-5)

5-2(45)

5-90

-85

User Dimson D
by
4.7k points
3 votes

Answer:


-85

Explanation:


-x+y(x-4)x


-\left(-5\right)+\left(-2\right)\left(\left(-5\right)-4\right)\left(-5\right)

Follow the PEMDAS order of operations:-

Calculate within the parentheses:-


\left(-5\right)-4


=-9


-\left(-5\right)+\left(-2\right)\left(-9\right)\left(-5\right)

Multiply:-


\left(-2\right)\left(-9\right)\left(-5\right)

Rule:-
(-a) * (-b)=a* b


2\cdot \:9=18


=18\left(-5\right)


18\left(-5\right)=-18\cdot \:5=-90


=-\left(-5\right)-90


-\left(-5\right)-90

Rule:-
-(-a)=a


-\left(-5\right)=5

Subtract:-


5-90


=-85

User Mxix
by
5.6k points